A Socio-ecological Framework for Understanding Workplace Violence in China’s Health Sector: A Qualitative Analysis of Health Workers' Responses to an Open-ended Survey Question - Wu, Dan (Journal of interpersonal violence, 2022)
Workplace violence (WPV) in the health sector is a global public health issue. The magnitude of WPV is a particular concern in China?s health system. To examine the potential causes of WPV, we analyzed 3,045 qualitative responses to an open-ended question in a survey with health workers in the Zhejiang province, China. We adapted a four-level socio-ecological framework (societal/systemic, community/organizational, interpersonal, and individual) to thematically analyze the data. Ten sub-themes emerged. Within the societal/systemic level, we identified three sub-themes: (a) lack of legislation against WPV, (b) suboptimal accessibility and affordability of health services due to maldistributed health resources, commercialized health services, and inadequate health insurance, and (c) unregulated mass media reports. Within the community/organizational level, three sub-themes emerged: (a) lack of supportive health facility leadership, (b) inaction by government authorities, and (c) inefficient law enforcement agencies. Within the interpersonal level, two sub-themes were identified: (a) poor provider?patient communication and (b) distrust between health workers and patients. Finally, we identified the personal characteristics of health workers (e.g., competence and professionalism) and patients (e.g., sociodemographic background and expectations/satisfaction) as two individual-level sub-themes.We recognized interactions among different levels. The weak state of Chinese legislation in this area and lack of high-level political will and guidance (societal/systemic) has left health facilities and law enforcement agencies (community/organizational) unclear about how to address WPV. The maldistribution of quality health resources (societal/systemic) has led to overcrowded outpatient clinics at higher-level care facilities (community/organizational). In light of the insufficient government funding and profit-oriented health services (societal/systemic), health workers were motivated to seek profits by providing unnecessary services, which compromised their professionalism (individual). Provider?patient relationships deteriorated (interpersonal), and patients sometimes held unrealistically high expectations associated with high medical expenses (individual). We propose multisectoral prevention strategies to address WPV in the health sector at all levels using a socio-ecological framework.